2024
DOI: 10.1021/acs.energyfuels.3c04371
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanocage Confining CuCo Bimetallic Interface with Low Nitrate Adsorption Energy for Highly Efficient Electrochemical Ammonia Synthesis

Jun Cheng,
Guorun Dai,
Weifu Sun
et al.

Abstract: This work aimed to improve the Faraday efficiency and formation rate of ammonia with a low reaction potential in the electroreduction of nitrate. For this purpose, CuCo bimetallic interface-rich catalysts confined in porous nitrogen-doped carbon nanocages (CuCo/NC) were designed. Results of in situ Fourier transform infrared spectroscopy suggested that the reaction path followed the sequence NO 3Density functional theory calculations revealed that the adsorption of nitrate over the CuCo bimetallic interface wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…In addition, the Co/NC-800 continued to have stable FE and NH 3 yields after 10 cycles of operation. Cheng et al immobilized CoCu bimetals in nitrogen-doped carbon nanocages. In situ Fourier transform infrared spectroscopy (FTIR) and density functional theory (DFT) showed that the introduction of Co metal promoted electron transfer and enhanced the tendency of hydrogenation of adsorbed intermediates at the Cu active site.…”
Section: Rational Selection and Design Of Electrocatalyst Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the Co/NC-800 continued to have stable FE and NH 3 yields after 10 cycles of operation. Cheng et al immobilized CoCu bimetals in nitrogen-doped carbon nanocages. In situ Fourier transform infrared spectroscopy (FTIR) and density functional theory (DFT) showed that the introduction of Co metal promoted electron transfer and enhanced the tendency of hydrogenation of adsorbed intermediates at the Cu active site.…”
Section: Rational Selection and Design Of Electrocatalyst Materialsmentioning
confidence: 99%
“…Recently, besides the studies on the above-mentioned noble metal alloy catalysts, additional studies have been conducted on double transition metal alloys as well as Cu-based alloy catalysts, such as Cu-Ni, Cu-Co, , Cu-Pd, , Co-Ni, , and Co-Fe. , Results on electrochemical nitrate reduction using other metal alloy catalysts have also been obtained. Zhang et al synthesized a CuNi nanoalloy catalyst (CFP-Cu 1 Ni 1 ) on carbon-fiber paper, which allowed the metal nanoparticles to be well dispersed and the elements to be uniformly mixed.…”
Section: Rational Selection and Design Of Electrocatalyst Materialsmentioning
confidence: 99%